Market Failure Factors And Risk Management Of Hydroponic Melons At Mantri Melon Farm - Asfarida, Tiara; Setiyani, Rahmawati; Sepfrian, Bimoseno (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
This study aims to analyze the factor that cause market failure at Mantri Melon Farm Agritourism and identify effective market risk management efforts. Mantri Melon Farm, as an agritourism destination that relies on hydroponic melon production, faces significant challenges in maintaining its market share. Through a qualitative approach, data was collected from interviews with the owner Mantri Melon, farmers and Mantri Melon employees. This research was conducted in May-June at Mantri Melon Farm Agrotourism. The results show that the main factor of market failure is asymmetric information. Efforts to overcome this are suggested with empowerment through education and increased literacy to have more equal access to information related to relevant issues, so that they are better able to make the right decisions, improve product quality, and maintain good relations with the market. The implementation of these strategies is expected to minimize market risk and ensure the sustainability of Mantri Melon Farm's business.